THE CONTRIBUTIONS OF TOURISM INDUSTRY TOWARD STUDENTS’ SPEAKING MOTIVATION IN LEARNING ENGLISH - Umar Umar; Suparman Suparman (Premise: Journal of English Education and Applied Linguistics, 2018)
This research aimed to find out The Contributions of Tourism Industry toward Students’ Speaking Motivation in Learning English on Students who live around Tourism Object. The participants of this research proposal is the students who live around tourism object (case study at Kencana Beach Cottages in Labuhan Badas Sumbawa Besar). The present study used mixed method. It contain to be examined in relation to quantitative and qualitative methods of data collection and analysis. The instrument used in collecting data was questionnaire, speaking test and observation.  Questionnaire and speaking test used descriptive statistics of frequencies and percentages. It was analyzed by using SPSS Program.Observation was analyzed by using qualitative method. Based on the data analysis technique above, it was found out the the contributions oftourism industry toward students’ speaking motivation in learning English and to know how the contribution of tourism industry toward students’ speaking motivation in English.